DC motors in automotive equipment: applications and challenges - Muhammad Nor Azril, Zulkafli; Mohd Azri Hizami, Rasid (UTeM, 2022)
The technological solution of hydraulic and pneumatic becomes obsolete in comparison to electric drive, mainly due to the efficiency, responsiveness, maintenance, and readiness for integration into a more intelligent system. In pursuing the electrification path, we have seen the integration of motors into more important applications such as steering, and braking among many more before taking the leap to replace the internal combustion engine to a traction electric motor. This paper reviews the main automotive applications that employ DC motor as actuator, and highlight the main issues and challenges in its implementation.